RETRACTED: Experimental determination of the thermal conductivity of building materials under operating conditions - Frolova Anastasiya; Ledovskikh Ilya; Panin Kirill; Ramazanov Eldar (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001